Scaffolds of the Church: Towards Poststructural Ecclesiology - Hovorun, Cyril (Wipf and Stock Publishers, 2017)
Unity is the categorical imperative of the church. It is not just the church's bene esse, but its esse. In addition to being a theological concept, unity has become a raison d'etre of various structures that the church has established and developed. All of these structures are supposed to serve the end of unity. However, from time to time some of them deviate from their initial purpose and contribute to disunity. This happens because the structures of the church are not a part of its nature and can therefore turn against it. They are like scaffolding, which facilitates the construction and mai